HLA genes in Barranquilla (North Colombia): Searching for cryptic Amerindian genes (2017)
America First Inhabitants population (Amerindians, Na Dene and Eskimos) underwent a drastic population reduction and gene exchange after Europeans and Africans arrival after 1492 AD. Barranquilla population may be a good model to study present day population admixture in South America. HLA-A, -B and -DRB1 DNA typing has been performed in 188 unrelated individuals originated in the area and speak Spanish language; they showed apparent European/African and mixed characters. HLA genetic European/African features were found and only 1.85% Amerindian one. This contrasts with neighboring Cuban population where 10% HLA Amerindian characters appear. © 2017.